Applying Press Law and Online Media Framing in the Case of Brigadier J .'s Murder - Syafriadi Syafriadi (Faculty of Law, Universitas Pekalongan, 2023)
This study analyzes the news framing of detik.com, tribunnews.com, and coil.com on the killing of Brigadier Pol Nofriansyah Joshua Hutabarat ( Brigadier J) from the perspective of legal politics in the application of Law Number 40 of 1999 concerning the press by using the theory of Robert N. Entman. It shows how the norms of the law are invited to be implemented in highlighting issues to attract readers' attention. This study uses a framing analysis method with a paradigm or construction approach, which views that there is no objective reality. The data collection technique in this study was carried out based on analysis and studies based on the news of the three media with the random sampling method. In addition, literature studies are also carried out through books, journals, articles, and the internet. The conclusion obtained from the results of this study is that detik.com, tribunnews.com, and coil.com both apply the straight news reporting model that is on actual issues to implement it as a social media control. This pattern of reporting helped push information about Brigadier J's murder into a wild ball outside of mainstream information.